Trends in the use of mango waste for the production of non-food materials (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Mango (Mangifera indica) is a tropical fruit widely consumed worldwide, leading to significant waste generation in the industry. These residues, mostly discarded, are used to obtain secondary foods such as pulps and juices, offering an unexplored potential for obtaining high-value biomaterials. This article analyses current trends in the use of mango waste for the production of biomaterials, including bioplastics, bioactive compounds and nanomaterials. It also highlights the importance of interdisciplinarity between agro-industrial chains and materials science.
Keywords: Co-Product; Utilisation; Mangifera indica